AB1344 Hospital infusion center costs for anti–tumor necrosis factor agents. (23rd January 2014) - Schmier, J.; Cifaldi, M.A.; Shaw, J.W.; Halpern, M.T.; Nickman, N.A.
Abstract : Background: Tumor necrosis factor (TNF)–inhibiting drugs are provided to patients with rheumatoid arthritis in the form of an intravenous infusion or subcutaneous injection. Although anti-TNF infusions are typically provided in hospital-based centers, the administrators of these centers often have limited understanding of the associated treatment costs. Objectives: To estimate the total cost of anti-TNF infusion care from a hospital perspective using an activity-based costing approach. Methods: An activity-based model was developed using several types of infusion center inputs: hourly wages, times to provide care, supply and overhead costs, laboratory test costs, infusion center size, and practice pattern information. The model assumed 8 infusions of infliximab annually. Base case values were derived from a survey of 5 community hospital infusion centers, previously published nurse and pharmacist time estimates, and expert opinion. Costs were derived from standard national sources. An overhead charge of 29.5% was applied to all costs. All costs were measured in or inflated to 2011 US dollars. Results: The total cost per infusion, including drug and laboratory costs, was estimated to be $3185. Most of this cost was attributable to the acquisition cost of the infused medication. Of the $427 not associated with drug, $93 was associated with recommended laboratory tests. Infusion costs—including labor and supplies associated with preparation, administration, and premedication and treatment of adverse events if necessary—were estimated at $334 per infusion. Of this amount, $121 was attributable to nonlabor categories (eg, capital equipment) and management (eg, inventory and documentation). In contrast, total Medicare reimbursement for a 3-hour infusion would be less than $120. A separate module including indirect costs (ie, lost productivity of patient and/or caregiver, transportation) estimated each infusion visit to be associated with an additional $146 cost to the patient. Conclusions: Although drug costs contribute most to the cost of anti-TNF infusion care, personnel, supply, and overhead costs can also be substantial. The model developed in this research can be used to quantify the total cost of providing anti-TNF infusion services so that financially responsible treatment strategies can be implemented at a given institution. In a market in which reimbursement and the efficient use of personnel are keenly important, such a tool can help hospital administrators make informed choices about the services to be offered and their financial implications. Disclosure of Interest: J. Schmier Employee of: Exponent, which received a research grant from Abbott, M. Cifaldi Shareholder of: Abbott, Employee of: Abbott, J. Shaw Shareholder of: Abbott, Employee of: Abbott, M. Halpern Grant/Research support from: Abbott, N. Nickman Consultant for: Exponent, which received a research grant from Abbott